Overview: Enzyme-catalyzed Enantioselective Biotransformation of Chiral Active Compounds Used in Hypertension Treatment - Chałupka, Joanna; Sikora, Adam; Kozicka, Aleksandra; Marszałł, Michał P. (Current Organic Chemistry, 2020)
Enzymatic kinetic resolution is one of the methods which allows for the synthesis of enantiomerically pure various active pharmaceutical ingredients. In contrast to chemical routes, enzymatic reactions have characteristics, including mild reaction conditions, a few byproducts, and relatively high activity of the used enzymes. β-adrenolytic drugs are widely used in the treatment of hypertension and cardiovascular disorders. Due to the fact that β- blockers possess an asymmetric carbon atom in their structure, they are presented in two enantiomeric forms. It was reported by many studies that only the (S)-enantiomers of these drugs possess the desired therapeutic effect, whereas the administration of the racemate may cause dangerous side effects, such as bronchoconstriction or diabetes. Nevertheless, β- blockers are still commercially available drugs mainly used in medicine as racemates, whereas there are several methods that are widely used in order to obtain enantiomerically pure compounds.
Keywords: lipase